A comparative analysis of biomechanical factors and premotor time of body muscles between elite college and amateur baseball players during the baseball batting motion - Lim, Y.-T.; Kwon, M.-S. (Korean Journal of Sport Biomechanics, 2016)
Purpose: The aim of this study was to analyze biomechanical factors and PMT (premotor time) of body muscles between elite college and amateur baseball players during the baseball batting motion. Method: Kinematic and electromyographic data were obtained for 10 elite college baseball players and 10 amateur baseball players who participated in this study. All motion capture data were collected at 200 Hz using 8 VICON cameras and the PMT of muscles was recorded using a Delsys Trigno wireless system. The peak mean bat speed and the peak mean angular velocities of trunk, pelvis, and bat with PMT of 16 body muscles were computed. These kinematic and PMT data of both groups were compared by independent t-tests (p < .05). Results: The pelvis, trunk, and bat showed a sequence of angular velocity value during baseball batting. The PMTs of right tibialis anterior, left gastrocnemius, external oblique, and erector spinae were significantly different between the two groups. Conclusion: The PMT of body muscles was related to the shifting of body and rotation of the pelvis and the trunk segment, and this action can be considered the coordinated muscle activity of the lower and upper body.